Social and economic activity of the enterprise: the role of internet marketing in crisis conditions - Pavlov, Kostiantyn (My University, 2025)
The rapid evolution of the economy and technological progress creates new conditions for interaction between businesses and consumers. In the digital era, the Internet has become a key channel of communication and information exchange, empowering companies to rethink their marketing approaches and integrate online tools to maintain their competitive position. The modern consumer is characterized by high information awareness, mobility, and demanding service quality. This requires businesses not only to engage their audience through digital platforms, but also to ensure effective interaction that builds trust and loyalty. Thanks to online marketing, businesses can strategically segment the market, optimizing advertising campaigns and reducing the cost of attracting new customers. The integration of online marketing with anti-crisis strategies, which are proactive measures taken to mitigate the impact of potential crises, opens up new avenues for stimulating the social and economic activity of companies through digital channels such as social media, e-commerce platforms, and online advertising. It also contributes to the development of long-term relationships with customers and partners, which is especially important in times of economic instability. The study of this issue is of practical importance for businesses seeking to remain competitive and adaptive in a dynamic market and is particularly relevant in view of the digital transformation of business and global economic challenges. Internet marketing tools used as part of an anti-crisis strategy play an important role in increasing the social and economic activity of an enterprise in times of economic instability. They ensure quick adaptation to the changing market environment, effective communication with the target audience and maintaining interest in goods or services. Most importantly, they help to maintain and strengthen customer loyalty, which is critical during crises, as a stable customer base provides the company with the necessary financial resources to overcome difficulties. This article defines the features of crisis management, considers the classification of marketing strategies for crisis management, analyzes the essence of Internet marketing, its advantages, such as cost-effectiveness and global reach, and disadvantages, such as potential for negative feedback and data privacy concerns, as a tool of crisis management strategy for increasing the socio-economic activity of enterprises in the context of economic instability; describes the key tools of Internet marketing and their impact on increasing the socio-economic activity of an enterprise in the context of economic instability.
Стрімка еволюція економіки та технологічний прогрес диктують нові умови взаємодії між бізнесом та споживачами. В епоху цифрових технологій інтернет став ключовим каналом комунікації та інформаційного обміну, що змушує компанії переосмислювати свої маркетингові підходи та інтегрувати онлайн-інструменти для збереження конкурентних позицій. Сучасний споживач характеризується високою інформаційною обізнаністю, мобільністю та вимогливістю до якості обслуговування. Це вимагає від бізнесу не лише залучення аудиторії через цифрові платформи, але й забезпечення ефективної взаємодії, що сприяє зміцненню довіри та лояльності. Завдяки інтернет-маркетингу підприємства отримують можливість більш точної сегментації ринку, що дозволяє оптимізувати рекламні кампанії та скоротити витрати на залучення нових клієнтів. Інтеграція інтернет-маркетингу з антикризовими стратегіями відкриває нові перспективи для стимулювання соціально-економічної активності компаній за допомогою цифрових каналів, таких як соціальні мережі, платформи електронної комерції та онлайн-реклама. Це також сприяє розвитку довготривалих відносин з клієнтами та партнерами, що є особливо важливим в умовах економічної нестабільності. Дослідження цієї проблематики має практичне значення для підприємств, які прагнуть залишатися конкурентоспроможними та адаптивними в умовах динамічного ринку, та є особливо актуальним з огляду на цифрову трансформацію бізнесу та глобальні економічні виклики. Інструменти інтернет-маркетингу, що застосовуються в рамках антикризової стратегії, відіграють важливу роль у підвищенні соціально-економічної активності підприємства в періоди економічної нестабільності. Вони забезпечують швидку адаптацію до мінливого ринкового середовища, ефективну комунікацію з цільовою аудиторією та підтримання інтересу до товарів або послуг. Крім того, вони сприяють збереженню та зміцненню лояльності клієнтів, що є критично важливим під час криз, оскільки стабільна клієнтська база забезпечує компанії необхідні фінансові ресурси для подолання труднощів. У даній статті було визначено особливості антикризового управління; розглянуто класифікацію маркетингових стратегій антикризового управління; проаналізовано сутність інтернет-маркетингу, його переваги та недоліки як інструменту антикризової стратегії для підвищення соціально-економічної активності підприємств в умовах економічної нестабільності; описано ключові інструменти інтернет-маркетингу та їхній вплив на підвищення соціально-економічної активності підприємства в умовах економічної нестабільності.
Keywords: social activity; economic activity; crisis; Internet marketing; enterprise activity; M3; H56; 339.138:004.738.5:330.131.7